The Effect of Interval Training on Developing The Endurance of Skill Performance In Long Rounds of Table Tennis - Hamdullah Abed Hammadi; Mohammed Obaid Jameel (Pubmedia Jurnal Pendidikan Olahraga, 2026)
This research aims to study the effect of interval training on developing endurance of skill performance during long rounds in table tennis. The researcher adopted the experimental approach by designing two groups (experimental and control), and implementing a training program based on a pattern of time repetitions and active and rest periods, in line with the specificity of continuous performance in open-time rounds. The research sample consisted of (20) players from the advanced youth category at Babylon Sports Club, aged between 17 and 19 years. The training program was implemented for a period of (6) weeks, with three training units per week. A special test was used to measure skill performance endurance, designed by the researcher. This test relies on executing a continuous series of serving, receiving, and hitting within a specified time, while calculating the number of errors and the time of decline in performance quality. The results of the statistical analysis showed statistically significant differences in favor of the experimental group in the skill endurance index compared to the control group, confirming the effectiveness of the interval training method in developing players’ ability to maintain the quality of technical performance during long rounds. The study recommends including this type of training in advanced player preparation, and conducting extensive studies on different age groups and technical levels to measure its impact in real-world playing situations.